Upaya Pencegahan Piracy Attack pada Kapal MV. X Saat Melintasi High Risk Area - Moch. Rizky Ramadhan; Iie Suwondo; Muhammad Dahri; Sutoyo Sutoyo (Pusat riset dan Inovasi Nasional, 2025)
This study discusses the preventive measures against piracy attacks faced by MV. X while transiting High Risk Areas. The purpose of this research is to identify the vessel’s vulnerability factors to piracy attacks and analyze the procedures and preventive actions that have been implemented. A descriptive qualitative method was used, including observation, in-depth interviews with crew members and armed guards, as well as document analysis of anti-piracy SOPs. The research findings show that the vulnerabilities of MV. X are due to limited drill training, suboptimal implementation of procedures, and inconsistency in the use of personal protective equipment (PPE). Based on these findings, it is recommended to increase the frequency and depth of simulation drills, enforce PPE usage standards, and update deck access security procedures. In conclusion, consistent implementation of procedures and structured training will enhance vessel security during High Risk Area transits.